Mycosphaerellaceous fungi and new species of Venustosynnema and Zasmidium on ferns and fern allies in Taiwan - Kirschner, Roland; Liu, Li-Chia (Phytotaxa, 2014)
Selected fungi on ferns in Taiwan are described, illustrated, annotated and complemented with first DNA sequences. The ranges of distribution, host species, morphology, and the taxonomy of some species were revised. ITS rDNA sequences proved to be useful for distinguishing between species on the same host. A new species of Venustosynnema found on dead leaves of Selaginella moellendorfii differs from the other species of the genus by its small conidiomata with smooth central seta and reniform conidia. A new species of Zasmidium described on living fronds of Dicranopteris linearis is particular by its hyaline, smooth conidia. New data are derived from new collections of Pseudocercospora athyrii, Ps. cyatheae, and Ps. pteridophytophila hitherto only known from the type collections and of Mycosphaerella gleicheniae. Ps. christellae is considered a synonym of Ps. pteridophytophila. M. gleicheniae and Ps. cyatheae are new records for Taiwan.